Computer-Assisted Language Learning Trends and Issues Revisited: Integrating Innovation - GARRETT, NINA (The Modern language journal (Boulder, Colo.), 2009)
This update to Garrett (1991), "Technology in the Service of Language Learning: Trends and Issues," explores current uses of technology to facilitate the teaching and assessment of second languages. In this article, I discuss the changes that have taken place over the last 18 years regarding selected topics from the 1991 article, including the relationship between pedagogy, theory, and technology, physical infrastructure, efficacy, copyright concerns, categories of software (e.g., tutorial, authentic materials engagement, communication uses of technology), and evaluation. I then explore the most challenging issues facing computer-assisted language learning (CALL) scholarship and practice today, that is, new demands in language education (based on the conclusions of the 2007 report of the Modern Language Association and Jackson & Malone, 2009), the need to rethink grammar instruction, online learning, social computing, teacher training and professional development, and CALL research. Like the original 1991 article, this work contains an appendix with links to information resources for CALL research and practice. I conclude by saying that new initiatives are needed to promote the use of technology for research on CALL and for facilitating second language acquisition, such as support for institutional language centers, streamlining of the work of professional organizations dedicated to CALL, and the establishment of a national CALL center.